2003
DOI: 10.1080/0036554021000028111
|View full text |Cite
|
Sign up to set email alerts
|

Speech Perception after Cochlear Implantation over a 4-Year Time Period

Abstract: The extent of hypometabolism as assessed by FDG-PET seemed to be one of the major factors predicting the outcome of cochlear implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 11 publications
5
57
1
10
Order By: Relevance
“…Speech perception results were better the longer cochlear implants were used, even though there were no statistically significant differences in duration of cochlear implant use and open and closed set speech recognition. Other authors have also pointed out a gradual development of speech perception abilities following cochlear implants use for some time in different groups of children [25][26][27][28][29][30][31][32][33] . The mechanism by which OAE deteriorate or are lost in AN/AD patients remains unknown; no significant relationship between absence and/or possible loss of OAE and any specific changes in AN/AD were found.…”
Section: Discussionmentioning
confidence: 99%
“…Speech perception results were better the longer cochlear implants were used, even though there were no statistically significant differences in duration of cochlear implant use and open and closed set speech recognition. Other authors have also pointed out a gradual development of speech perception abilities following cochlear implants use for some time in different groups of children [25][26][27][28][29][30][31][32][33] . The mechanism by which OAE deteriorate or are lost in AN/AD patients remains unknown; no significant relationship between absence and/or possible loss of OAE and any specific changes in AN/AD were found.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on cochlear implants in postlingual deaf patients also show an influence of the duration of deafness on functional outcome, especially speech perception: Oh et al 44 report 5 years of deafness as critical, whereas Durisin et al 12 found significant differences when comparing scores from before and after 6 months of deafness; also, over long training periods patients could not catch up in speech recognition. Peasgood and colleagues 50 found no speech recognition in adults with late cochlear implants, and much less favorable results than are associated with cochlear implants in general.…”
Section: Duration Of Preimplant Deafnessmentioning
confidence: 99%
“…Most authors discuss periods of a few years to more than 10 years, and advocate ABI surgery before 10 years of deafness. 3 Corresponding to experiences with cochlear implants, 12,44 durations of a few years must be considered and might decide whether there will be any hearing sensation at all. High-quality hearing, however, is dependent on much shorter periods.…”
Section: Duration Of Preimplant Deafnessmentioning
confidence: 99%
“…O desenvolvimento da percepção de fala e aquisição de linguagem, bem como, o sucesso da reabilitação, nas crianças com deficiência auditiva pré-lingual ou adultos com deficiência auditiva, pré ou pós-linguais, depende de alguns fatores determinantes como: tempo de privação auditiva, modo de comunicação ou tipo de reabilitação, etiologia e época da instalação da surdez, expectativa e motivação dos pais, paciente e terapeuta, engajamento da família na reabilitação. 2,6,9,10,11 O trabalho com o Deficiente Auditivo é enfáti-co no treino das habilidades auditivas.…”
Section: -Introdução Deficiência Auditivaunclassified